EXPRESSION OF CONCERN: Innovative Application of Computer Vision and Motion Tracking Technology in Sports Training - Changqing Liu; Xie, Yanan (EAI Endorsed Transactions on Pervasive Health and Technology, 2024)
EXPRESSION OF CONCERN: Concerns have been raised over the peer review and editorial processes involving this article. The full notice can be found here: Concerns have been raised over the peer review and editorial processes involving this article. The full notice can be found here: https://doi.org/10.4108/eetpht.11.12685